Complexes Accounting in light of international accounting standards and The accounting financial system – Case Study Saidl Complexe - berrik, Ahmed; ferdjallah, Ahlem (Journal of Research in Finance and Accounting, 2026)
This research aims to know the accounting compilation of the financial statements, because of its importance in giving an honest picture of the status of the compound and considering it an effective element that helps in decision-making, by clarifying the methods of accounting compilation of the financial statements. The study concluded that the Saidal complex in the process of accounting compilation of the financial statements in relation to the method of total consolidation is carried out on the basis of the percentage of capital contribution, not on the basis of the relationships between companies and the agreements concluded between them as stated in the IFRS10.